2021
DOI: 10.1177/17588359211006950
|View full text |Cite
|
Sign up to set email alerts
|

KRAS/LKB1 and KRAS/TP53 co-mutations create divergent immune signatures in lung adenocarcinomas

Abstract: Lung adenocarcinomas exhibit various patterns of genomic alterations. During the development of this cancer, KRAS serves as a driver oncogene with a relatively high mutational frequency. Emerging data suggest that lung adenocarcinomas with KRAS mutations can show enhanced PD-L1 expression and additional somatic mutations, thus linking the prospect of applying immune checkpoint blockade therapy to this disease. However, the responses of KRAS-mutant lung adenocarcinomas to this therapy are distinct, which is lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 72 publications
1
35
1
Order By: Relevance
“…15 The underlying mechanisms are associated with deficient DNA damage caused by TP53 mutations, thus giving rise to increased genetic mutations and immunogenicity of cancer cells. 16 Meanwhile, KRAS-TP53 co-mutations increase PD-L1 expression and infiltrating immune cells than KRAS-only or TP53-only mutations, indicating a synergistic effect. 16 Similarly, we found that patients with KRAS-TP53 co-mutations had the highest ORR following immunotherapy among patients with CHOL with varied combinations of KRAS and TP53 mutation status.…”
Section: Open Accessmentioning
confidence: 98%
See 1 more Smart Citation
“…15 The underlying mechanisms are associated with deficient DNA damage caused by TP53 mutations, thus giving rise to increased genetic mutations and immunogenicity of cancer cells. 16 Meanwhile, KRAS-TP53 co-mutations increase PD-L1 expression and infiltrating immune cells than KRAS-only or TP53-only mutations, indicating a synergistic effect. 16 Similarly, we found that patients with KRAS-TP53 co-mutations had the highest ORR following immunotherapy among patients with CHOL with varied combinations of KRAS and TP53 mutation status.…”
Section: Open Accessmentioning
confidence: 98%
“…16 Meanwhile, KRAS-TP53 co-mutations increase PD-L1 expression and infiltrating immune cells than KRAS-only or TP53-only mutations, indicating a synergistic effect. 16 Similarly, we found that patients with KRAS-TP53 co-mutations had the highest ORR following immunotherapy among patients with CHOL with varied combinations of KRAS and TP53 mutation status. Moreover, patients with KRAS-only mutations had the worst prognosis and immunotherapy outcomes.…”
Section: Open Accessmentioning
confidence: 98%
“…KP tumors showed higher levels of somatic mutations (although the smoking burden of the included patients was similar in all three subgroups), inflammatory markers, immune checkpoint effector molecules, and longer relapse-free survival (26,27). Subsequently, Skoulidis analyzed the efficacy of antiPD-1 in advanced lines and observed higher responses in the KP versus KC subgroup (35.7% vs 7.4%), identifying STK11 as an antiPD-1 resistance mutation (28).…”
Section: Co-mutational Status Of Krasmentioning
confidence: 99%
“…Prevalence of KRAS mutation 97.7% [9] 44.7% [9] 30.9% [9] Hottest missense mutation in KRAS G12D [9] G12D [9] G12C [9] Sensitive to glucose restriction vs. KRAS wt Yes [19] Yes [20] No [21] Common alteration with KRAS TP53 inactivation [10] TP53 and APC inactivation [22] TP53 or LKB1 inactivation [23] General milieu of KRAS-mutant tumors Immune-cold [7] Immune-cold [24] KRAS-only: immune-cold or hot [23] TP53 inactivation: immune-hot [23] LKB1 inactivation: immune-cold [23] Number General response to monotherapy using ICB drugs Poor [5] Poor [28] KRAS-only tumor: Fair [23] TP53 inactivation tumor: Excellent [23] LKB1 inactivation tumor: Poor [23] Core molecular events associated with KRAS mutation-induced immunosuppression 1. YAP-TAZ activation [12]; 2.…”
Section: Pdac Crac Luacmentioning
confidence: 99%
“…Nevertheless, KRAS mutation should not be regarded as a marker indicating immunosuppression in LUAC tumors because the immune milieu in KRAS-mutant LUAC tumors is heterogeneous. For example, the KRAS/LKB1 and KRAS/TP53 co-mutations enable LUAC patients to have dramatically different responses to ICB therapy because these two mutational patterns generally create a unique immune milieu in tumors (see details in [23]). Collectively, KRAS mutation can affect the cancer immune state in PDAC, CRAC and LUAC in different ways and contextures (Table 1).…”
Section: Value Of Kras Mutation For Predicting Cancer Immune Status In Other Adenocarcinomasmentioning
confidence: 99%